Solid waste generation characteristics: The Malaysian local authorities’ outlook - Abu Eusuf, Muhammad; Ibrahim, Mansor; Mohd. Din, Shamzani Affendy; Islam, Rafikul (Malaysian Institute Of Planner, 2011)
The large and increasing amounts of municipal solid waste (MSW) generated each year in several industrialised countries have raised concerns on the economic viability and environmental acceptability of the current generation activities. The planning of an optimal regional waste management strategy requires a reliable tool for predicting the amount and the corresponding composition of MSW likely to be produced. Furthermore, for integrated solid waste management, direct and indirect participation of local government’s authority is essential. This paper focuses on the existing waste management characteristics of selected local authorities in Malaysia. As a case study, the research considers three local authorities in Selangor State, namely Selayang, Klang and Subang Jaya. This research further identifies the issues concerning the environmental effects due to indiscriminate solid waste disposal. The findings of the study are expected to provide useful guidelines to the MSW policy makers.